PENGARUH MEDIA POP UP BOOK TERHADAP KETERAMPILAN MENULIS SISWA PADA MATA PELAJARAN BAHASA INDONESIA SD - Isna Ilvi Nurrohmah; Suharmono Kasiyun; Nafi'ah Nafi'ah; Muhammad Taufiq (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2020)
The purpose of this research is to use of pop up book media for writing skills in Indonesian primary school subjects. The method used in this research is meta-analisys method. This research begins by formulating the topic to be examined, than make a statement of the problem, and than stage the collection of relevant articles to collect data. The data is obtained from online journal searches through Google Scholar. The keywords used are “Pop up book” and “elementary school writing skills”. From search results there are 8 articles. The data obtained were analyzed again using quantitative method. Based on the results of Pop Up Book media analysis it can be proven to improve students’ writing skills by an average before being given treatment is 57.58 and after being given treatment is 76.05 so that increases is 18.47.Keywords: Pop up Book Media,  Skills Writing, Indonesian